AN INTERACTIONAL COMMUNICATION BETWEEN PARENTS AND THEIR CHILDREN TO EMBEDDING MALAY LANGUAGE - Putri, Meiliza Eka; Yohana, Nova (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Riau is malay land which is inhabited by millions of active supporters of the malay culture, especially in villages that still adhere to the traditions/customs, their heritages one of which is the language. Cultural aspects that would occupy the main priority to be fostered, developed, and then inherited is a local language. However, the most alarming is the mutation of local language in the family. This concern emerges because the family uses the informal language as priority, where the children should acquire it in the first time and the longest time. This research has been made for the goal knowing the communicative situation, communicative events and communicative action between parents and their children in embedding the malay language.This research used descriptive qualitative research methods, the ethnography of communication approach that examines the role of language in communication behavior of a society, that is the way how the language is used in different cultural communities. The selection of informants using purposive sampling techniques and snawball, which selects five selected informants are female characters wither and chairman of the board of LAM daily Riau as key informants, in the coastal village headman, and two families. The data collection techniques are used observation, in-depth interviews, and documentation. For the data analysis was refer to the interactive model of Huberman and Miles. For checking the validity of data were using triangulation and extension participation techniques.From this research concluded that communicative situation of parents and children in the malay language instilled in doing home and family events. Communicative events and daily routines based on the same genre such informationJom FISIP Volume 2 No. 1 – Oktober 2014 Page 2and the same time. Where as in communicative acts ranging from the familyenvironment is done repeatedly (habituation).Key words : Komunikasi Interpersonal, Komunikasi Interaksional, Bahasa Melayu